2015
DOI: 10.1080/00071668.2015.1041453
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evaluation of carcass traits in Japanese quail using ultrasonic and morphological measurements

Abstract: 1. A study was conducted to evaluate the carcass composition of 1083 live birds using ultrasonic and morphological measurements and to estimate the genetic relationship between predicted and dissected carcass composition in Japanese quail. 2. Birds were reared for 35 d, and morphological measurements consisting of the length and width of breast muscle were recorded for all birds using a digital caliper. After slaughtering, the weight and percentage of carcass traits were measured on chilled carcasses. The dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…Having obtained similar results, Walite et al [53] reported that the mean values of the breast, leg and wing were 29.1%, 15.9% and 11.8%, respectively. Akbarnejad et al [54] found lower averages than the mean values determined in this study, and the yield of cold carcass, breast and leg were found to be 65.0%, 24.7% and 15.1%, respectively. Egg production, fertility, early, late and total embryonic death rates and mean analysis of variance are given in Table 6.…”
Section: Discussioncontrasting
confidence: 64%
“…Having obtained similar results, Walite et al [53] reported that the mean values of the breast, leg and wing were 29.1%, 15.9% and 11.8%, respectively. Akbarnejad et al [54] found lower averages than the mean values determined in this study, and the yield of cold carcass, breast and leg were found to be 65.0%, 24.7% and 15.1%, respectively. Egg production, fertility, early, late and total embryonic death rates and mean analysis of variance are given in Table 6.…”
Section: Discussioncontrasting
confidence: 64%
“…However, the present study found that it is profitable to raise quails for the first five weeks of age because the weight gain progress attends its highest ratio in this short period of life. On the other hand, several reports were suggested that the LBW was affected by the gender of the birds (1,17). This is since females are bigger in body size than males, so it is profitable to be raised after two sexes̓ separation.…”
Section: Table 1 Effect Of the Line Of Japanese Quails On Live Body Weight (Lbw)mentioning
confidence: 99%
“…Akbarnejad et al 14 worked with a genetic evaluation of carcass traits in Japanese quails using ultrasound and morphological measurements and observed that the estimation of the breast ultrasound image had a high genetic correlation with the estimation of morphological measurements performed after slaughter. The authors further stated that breast muscle ultrasound measurements could effectively predict breast weight and performance in Japanese quails.…”
Section: Discussionmentioning
confidence: 99%
“…For the analysis of the data from the ultrasound of the birds, the SAS 14 program was used. The measurements were analyzed using multiple linear regression (Proc.…”
Section: Methodsmentioning
confidence: 99%